ANALISIS PENILAIAN TINGKAT KESEHATAN BANK DENGAN MENGGUNAKAN METODE RGEC PADA BANK UMUM SWASTA NASIONAL DEVISA YANG TERDAFTAR DI BEI - Avissa Benita Elizabeth Tamba; Luk Luk Fuadah; Aryanto Aryanto (AKUNTABILITAS, 2018)
This study aims to determine the health level of National Private Foreign-Exchange Commercial Bank in 2012 to 2016 in terms of Risk profile, GCG, Earnings, Capital, and RGEC as a whole. The type of this study is evaluative research with the subject of National Private Foreign-Exchange Commercial Bank Listed On Indonesia Stock Exchange in 2012 to 2016. Data obtained through documentation techniques. Data analysis technique used is Risk-Based Bank Rating, with scope of assessment covering RGEC factors. Variable of Risk Profile measured by NPL and LDR ratios, GCG measured by self assessment from companies, Earning measured by ROA and NIM ratios, and Capital measured by CAR ratio. The results of research showed National Private Foreign-Exchange Commercial Bank in 2012 to 2016 as a whole get healthy predicate.